Can we do more than case studies? A scoping review about qualitative research in sport management in the Brazilian context - Yves Miranda; Jorge Eduardo Maciel Gonçalves Silva; Marcos Barros Filho; Carlos Augusto Mulatinho de Queiroz Pedroso (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: In the past two decades, sport management research in Brazil has progressed, but there are some issues hindering this development. Despite associations and dedicated journals, studies commonly face theoretical and methodological challenges. To date, there has not been an extensive discussion on the development of sport management research in Brazil, particularly those utilizing a qualitative approach. Objective: The aim of this article was to systematically map the scientific literature on qualitative research in the field of sport management in Brazil. Methodology: Using Arksey and O'Malley's framework, a scoping review was conducted on articles from major English and Portuguese journals (2000-2022), identifying 115 qualitative studies. Results: Frequency analysis demonstrated most studies used case studies or the type of qualitative research was not identified. A thematic analysis indicated a concentration and possibilities for expanding research themes, as well as the need to employ contemporary qualitative methods in sport management research within the Brazilian context. Discussion: The results largely align with studies analyzing qualitative research in sport management in the international context. However, the findings provide insights into future directions for research in sport management within the Brazilian context.